EXPLORING ETHNICALLY DIVERSE STUDENTS’ REFLECTIONS ON INTERCULTURAL COMPETENCE IN A PUBLIC MALAYSIAN UNIVERSITY - Nor Hanim Mustafa; Nur Rasyidah Mohd Nordin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This paper explores the Malaysian undergraduate students’ narratives on intercultural competence in interactional context based on their personal reflections. Specifically, the paper attempts to make sense of how undergraduate students and their peers experience their multicultural interaction in campus setting. We argue that there is a need to understand how students manage their undergraduate work in multicultural interactional context and way of expressing opinions through the reflections of their own experience. Such a study can further assist not only students but also the educators in ensuring that students engage in a very productive academic collaboration with each other. Based on a pilot study data among selected students of multicultural background in a Malaysian campus, individual reflections and a focus group interview was conducted. The results were analysed and used to construct and fine-tune the research questions for in-depth interviews in the doctoral study proper. The study hoped to contribute to the field of teaching and learning particularly in intercultural interaction realm through the narrative inquiry in an attempt to provide harmony interaction between multicultural students. The paper concludes with several potential implications towards fine-tuning the standard of practice or ethical conduct of teaching and learning that enables to benefit both the faculty members and undergraduate students.